Pengembangan Media Edukatif Make a Match terhadap Keterampilan Sosial Siswa Menengah Pertama: Development of Make a Match Educational Media for Junior High School Students' Social Skills - Venia Ramadhani; Hendro Yulius Suryo Putro; Ali Rachman (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Social skills are an important competency that needs to be developed in junior high school students. However, in learning practice, educational media that encourage active student interaction, communication, and cooperation remain needed. Given these conditions, it is necessary to develop learning media that capture students' attention and support the process. This research was conducted using a research and development approach through the 4D model stages, namely define, design, develop, and disseminate. The media developed was an educational game card titled "Make a Match." The feasibility of the media was assessed through validation by material experts and media experts.In contrast, the practicality of the media was reviewed through a questionnaire of teacher responses as observers and student responses represented by the class leader. Based on the validation results, the feasibility of the developed media was 90.90% among material experts and 94.66% among media experts, both classified as very feasible. At the dissemination stage, the teacher response was 100%, and the student response was 98.33%, indicating that the media is very practical and received a positive response from users. The Make a Match educational media developed can be used as a learning tool and to support guidance and counseling services in junior high schools, demonstrating good feasibility and practicality. This media also aligns with Riggio's theory of social skills because the game activities encourage students to practice communication, cooperation, and social interaction.